Удосконалення системи оцінки складності нового гірничошахтного устаткування очисних вибоїв - Косарев, В.В. (Економіка промисловості, 2013)
Запропоновано рекомендації щодо удосконалення принципів оцінки складності гірничошахтного устаткування очисних вибоїв, що мають застосовуватися при проведенні приймальних випробувань дослідних зразків.
Ключові слова: вугільна шахта, устаткування, дослідний зразок, промислові випробування, оцінка складності техніки, вугільний вибій. Предложены рекомендации по совершен-ствованию принципов оценки сложности горно-шахтного оборудования очистных забоев, которые должны применяться при проведении приемочных испытаний опытных образцов.
Ключевые слова: угольная шахта, оборудование, опытный образец, промышленные испытания, оценка сложности техники, угольный забой. The results have been obtained on the basis of studying the domestic experience in the acceptance tests of test samples of a new mining equipment, the development of the standard of Minenergougleprom of Ukraine SOU-P “Products of coal engineering. Acceptance (exploitation) testing of experimental new (updated) samples. The order of organization, financing, economic and financial incentives for their implementation” made by the institute “Dongiprouglemash”, Institute of Industrial Economics of NAS of Ukraine and Donetsk Research Coal Institute and careful consideration of the issue of estimation of the degree of complexity and degree of novelty of the equipment that has a significant impact on the content and organization of industrial tests of the mining equipment.
The development of methods for estimation of the degree of complexity of the test sample began with the consideration of the integrated estimation of the importance and category of the equipment complexity in the process of its creation that was offered during the previous stages of the study, at the stage of industrial tests with the proposal to plan and standardize the assembling works taking into account the novelty and complexity of the tested equipment. At these stages of finishing the tested equipment, when the object of standardization and planning is the works on the elimination of the identified design defects and failures of the equipment, disassembling, delivery, assembling, revision, adjusting its parts as a form of reflection of cost standards for workers’ labor, it was recommended to apply the normalized work quotas taking into account the coefficients established for a shift, day or other period for the brigade as a whole, separate links or groups of workers. In the previous stages of the study it was suggested to choose the factors, which stipulated the necessity of application of correcting coefficients, the number and boundaries of their gradations by expert estimation to involve the research workers, coal engineering plants, scientists, employees of the normative-research stations and experienced practical workers, i.e. those who knew the problem very well.
Taking into account all the above, to develop the project of standard of Minugleprom of Ukraine of 2011 the following factors of estimation of complexity of the test sample were selected: the number of automated functions in the product, the number of positions (part types), the number of energy subsystems (mechanical, electric, pneumatic, hydraulic), mass of the product (in kilograms), the biggest size (length, width or height, mm). Each of these factors alone only partially reflects labour input in the servicing of equipment, the range of necessary professional knowledge and volume of necessary skills, but together they adequately characterize the degree of complexity of the sample of equipment.
Based on the acquaintance with the known samples of existent mining equipment in Ukraine and abroad, the information published in the special editions and on the forecasts of skilled experts, the existent and expected in the near future marginal values of the above factors of complexity have been established, and the number of gradations for each element of complexity has been defined, numerical parameters of which are presented in the standard of Minugleprom of Ukraine of 2011. So, into account was taken the improved classification of new equipment according to the degrees of its complexity, importance and integrated estimation-category of equipment.
Over the term of the standard of Minugleprom of Ukraine of 2011 some provisions of the methodology for estimation of the equipment complexity have been identified, which should be specified in the further use of the Standard.
Principles of estimation of the new mining equipment complexity have been identified, which must be used in industrial testing of experimental and test samples.
The above proposals on the improvement of the system of estimation of complexity of new mining equipment for breakage faces will facilitate the continuation of the process of forming of normative and methodical recommendations on organization of industrial tests of mining equipment. In the future, the searches for effective systems of payment for labour in testing and introduction of new equipment will be also conducted, using the estimation of complexity of studied mining equipment. Practical application of the developed Standard will allow getting some proposals concerning this issue.